Frequency of occurrence and antimicrobial susceptibility of bacteria isolated from respiratory samples of patients hospitalized with pneumonia in Western Europe, Eastern Europe and the USA: results from the SENTRY Antimicrobial Surveillance Program (2016–19). Issue 3 (2nd September 2021) - Sader, Helio S; Streit, Jennifer M; Carvalhaes, Cecilia G; Huband, Michael D; Shortridge, Dee; Mendes, Rodrigo E; Castanheira, Mariana
Abstract: Background: The SENTRY Antimicrobial Surveillance Program monitors the frequency of occurrence and antimicrobial susceptibility of organisms from various infection types worldwide. Objectives: To evaluate the SENTRY programme results for organisms isolated from respiratory samples of patients hospitalized with probable pneumonia. Methods: A total of 28 918 bacterial isolates were consecutively collected (one per patient) in 2016–19 from 121 medical centres located in western Europe (W-EU; n = 7966), eastern Europe (E-EU; n = 3182) and the USA ( n = 17 770) and then susceptibility tested by reference broth microdilution methods in a central laboratory. Results: Gram-negative bacilli (GNB) represented 76.3%, 88.6% and 69.1% of organisms; non-fermentative (NF) GNB accounted for 26.9%, 51.8% and 34.6% of organisms in W-EU, E-EU and USA, respectively. Pseudomonas aeruginosa susceptibility to piperacillin/tazobactam and meropenem was 75.4% and 76.9% in W-EU, 57.4% and 48.3% in E-EU, and 76.1% and 74.8% in the USA, respectively. Only 10.4% of Acinetobacter baumannii isolates from E-EU were meropenem susceptible compared with 45.8% in W-EU and 58.8% in the USA. Overall MRSA rates were 21.4% in W-EU and 28.7% in E-EU. In the USA, MRSA rates decreased from 44.8% in 2016 to 40.1% in 2019. Carbapenem resistance among Enterobacterales decreased continuously in the USA from 3.0% in 2016 to 1.7% in 2019 (2.4% overall) and was higher in E-EU (16.6%) than W-EU (2.2%). Klebsiella pneumoniae susceptibility to meropenem was 91.3%, 72.5% and 95.3% in W-EU, E-EU and the USA, respectively. Conclusions: Rank order and antimicrobial susceptibility of bacteria isolated from patients with pneumonia widely varied by geography. MDR NF-GNB represented an important cause of pneumonia.